Dynamic modelling and natural characteristics analysis of fluid conveying pipeline with connecting hose. (15th June 2023) - Cao, Yiming; Guo, Xumin; Ma, Hui; Ge, Han; Li, Hui; Lin, Junzhe; Jia, Duo; Wang, Bing; Ma, Yongchun
Abstract: As an important connecting component, the hoses transport fluid from pump to pipeline. However, the modeling of connecting hose has been rarely incorporated in the open research of pipeline modeling. To study the natural characteristics of fluid conveying pipeline and the effect of the connecting hose, a new dynamic model of pipeline with connecting hose is established by the finite element method. The measured support stiffness of clamp is introduced, and the equivalent boundary stiffness of connecting hose is identified based on the genetic algorithm (GA) and the measured frequency response function. The proposed model is verified by numerical examples and experimental results. Besides, the mixed finite element method (using shell element and fluid element) and the transfer matrix method are used to verify the natural characteristics of the proposed model under different fluid excitation. Moreover, the effect of fluid pressure on natural frequency of pipeline is analyzed. The results show the proposed model has higher precision than other models, and the average error is 0.55%. When the pressure increases from 0 MPa to 15 MPa, the natural frequency of pipeline decreases and the decline rate decreases with the increase of modal order. This paper provides the theoretical and experimental basis for the practical engineering requirements, and the proposed model can be more comprehensive to study the natural characteristics in fluid conveying pipeline.